Lean and Ergonomics decision support tool assessment in a plastic packaging company - Brito, Marlene (2020)
This paper intends to apply and improve a workstation assessment tool called ErgoSafeCI. Lean manufacturing methods and guidelines, together with safety and ergonomics aspects, were thoroughly researched with the ultimate objective of finding a way to improve the workplace by considering the efficiency and well-being of workers. The assessment tool was applied in the plastics packaging sector, in a process which relied on both practical and theoretical ideas. This tool originates in the notion that for a successful Lean implementation, managers should start the Lean process with a Lean assessment which is then repeated on a regular basis. In addition, it is also important to integrate ergonomic conditions in this journey because ergonomic risks can sometimes result in Lean wastes and vice versa, so workplace ergonomics and Lean manufacturing are to a great extent inter-related. This tool aids practitioners in the assessment of the implementation of Lean principles and safety matters in their processes.